Contribution of Career Guidance and Counseling Services to the Development of Student Career Commitment - Dewantara, Muhammad Rafli; Lesmana, Gusman (Medan State University, 2023)
The researcher's aim is to determine the contribution of career counseling services to the development of career commitment of students at SMK Negeri 14 Medan. The sampling technique is Purposive Sampling technique. To obtain definite and relatively fast data in collecting data or information, researchers use instruments in the form of observations and questionnaires. Based on the data above regarding the contribution of career counseling services to the development of career commitment of students at SMK Negeri 14 Medan as many as 35 people with a total of 55 items. After being tested for validity and reliability, there are 38 valid items. So from the data analysis it has been proven that there is a significant relationship among the students of SMK Negeri 14 Medan. This is shown by the correlation obtained from the SPSS model summary display showing the magnitude of the product moment (Pearson) correlation of the lowest score = 65, the highest = 139, average mean = 108.28 and Standard Deviation (SD) = 15.63. If the guidance and counseling services in the career sector are able to develop career commitment as well and as maximally as possible, it can prevent student disengagement in choosing a future career.